Effect of micro-osteoperforations on rate of space closure by mini-implant supported maxillary anterior en-masse retraction: A randomized clinical trial - Pradeep Raghav; Amit kumar Khera; Pranav Bhasin (Elsevier, 2021)
Background: Micro-osteoperforations is one of the non-invasive surgical techniques used in attempt to accelerate OTM. Conflicting reports on its effectiveness has been reported in the literature. Objectives: The objectives of this trial were to investigate the effect of micro-osteoperforations on the rate of space closure and on molar anchorage loss during mini-implant supported maxillary anterior en-masse retraction. Trial design: A single center, parallel arm, randomized controlled trial was conducted. Method: Sixty, male and female subjects (age range 16-25 years) having Class I bimaxillary protrusion or Class II div 1 malocclusion, who required fixed mechanotherapy with either upper 1st premolar or all four 1st premolar extractions were allocated into two groups using 1:1 allocation ratio. The allocation was done by block randomization method with a block size of 6. In the experimental group, 5 MOPs per side were performed only once just before the en-masse anterior retraction. Mini-screws were placed in order to obtain maximum anchorage. Impressions were taken every month till 4 months and rate of space closure was measured on 3D study models. Results: Data of 27 subjects in control (attrition ​= ​3) and 28 subjects in experimental group (attrition ​= ​2) were analyzed at the end of this trial. There was a statistically significant increase in the rate of en-masse retraction for the 1st month(p ​= ​0.001,95%CI, 0.17, 0.37 ​mm) but there was no statistically significant difference for the subsequent 2nd (p ​= ​0.450,95%CI,0.13,0.43 ​mm), 3rd(p ​= ​0.204,95%CI,0.23,0.47 ​mm) and 4th month (p ​= ​0.680,95%CI,0.21,0.41 ​mm) between experimental and control groups. There was also no difference (p ​> ​0.05) in molar anchorage loss between both groups at all time intervals. Conclusion: Micro-osteoperforations (MOPs) did not accelerate the rate of anterior en-masse retraction over a period of 4 months; however, it temporarily increases the rate of retraction only for first month and no affect on molar anchorage. Trial registration: The trial was registered at www.ctri.nic.in with CTRI No- CTRI/2019/03/018140).